Synthetic stereo acoustic echo cancellation structure for multiple participant VoIP conferences. - Yensen, T.N (IEEE Transactions on speech and audio processing)
This paper proposes a novel acoustic echo cancellation structure intended for multiple participant, full-duplex, hands-free voice over Internet protocol (VoIP) conferencing. A synthetic stereo image is generated through the use of spatialization functions, which are used to assist the near-end user in distinguishing between far-end talkers. The proposed synthetic stereo structure, which uses a single echo canceler per spatial region, is compared to structures with a single echo canceler per channel and to stereophonic echo cancelers. The proposed structure does not suffer from correlation of the reference signals, which can cause system misconvergence in structures that use a single canceler per channel. Correlation of the reference signals is eliminated since monaural signals are transmitted at the far-end and static spatialization functions are used at the near-end to allocate each participant to a spatial region